Effect of nasal irrigation on eosinophil and recurrence in allergic rhinitis - Sulistyanto, Agung; Wardani, Andriana Tjitria Widi; Maharani, Virgi Mayang (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Until now, the treatment of allergic rhinitis has not been satisfactory. Patients with allergic rhinitis are highly dependent on medical pharmacological treatment. Nasal irrigation is expected to help reduce symptoms due to decreased eosinophil counts and recurrence of allergic rhinitis. This study aims to determine the effect of nasal irrigation on eosinophils and the recurrence of allergic rhinitis—experimental research by pre – post-test group design. Twenty samples of allergic rhinitis patients were trained to wash their nose once a day at home—nasal mucosal secretion was collected to count eosinophils before and after intervention. The degree of recurrence was assessed based on the symptoms of nasal congestion, runny nose, sneezing, and itchy nose. The degree is divided into three groups: decrease, remain, and increase. The statistical analysis used in this study for bivariate analysis was Wilcoxon Test. There was a significant decrease in eosinophil count (p = 0.00) and recurrence of nasal congestion (p = 0.00), runny nose (p = 0.00), sneezing (p = 0.001) and itchy nose (p = 0.00) in allergic rhinitis after nasal irrigation intervention. Nasal irrigation treatment can help decrease eosinophil count and recurrence of allergic rhinitis.